Kína geopolitikai és geoökonómiai stratégiája az Északi-sarkon új régiós nagyhatalom a láthatáron? - Zoltai Alexandra (Egyesület Közép-Európa Kutatására Szeged, 2020)
As an area rich in unexplored resources, the North Pole is assuming an increasingly important geoeconomic and geopolitical role among Arctic and non-Arctic states, China is among the interested non-Arctic states. Mostly thanks to this, new trade routes have emerged in the region, which saves energy and time as a considerable security and geopolitical aspect. China has been working on building its regional ambitions for several years and released china’s Arctic Policy in early 2018, according to which the country would like to integrate this region into the New Silk Road Project, too. As China has a far weaker power position in the region than America or Russia, it will need cooperation and economic investment to enforce its interests. However, from the Chinese government’s perspective, the polar regions belong to the common heritage of humankind which means that all states should have the right to participate in, and shape, their future global governance. This paper analyzes China’s polar strategy, currently in the stage of doctrine formation and implementation, as a framework for understanding China’s global ambitions. It also examines the extent to which existing polar regimes will be able to cope with the changing balance of power and other new pressures. Arctic areas can be game changer for global connectivity which can also have an impact on Central and Eastern European Countries including Hungary.
Keywords: Társadalomtudományok; Politikatudomány; Társadalom- és gazdaságföldrajz